HEK 222- Critical Reading And Writing June 2016 - PPIK, Pusat Pengajian Ilmu Kemanusiaan (Universiti Sains Malaysia, 2016)
UNIVERSITI SAINS MALAYSIA Second Semester Examination 2015/2016 Academic Session June 2016